ACP bananas: Brussels clutches blanket quota - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The ACP-EU agreements on bananas have been under threat from the World Trade Organisation, following pressure from the United States, and producers represented by three major multinational corporations and four Latin American countries (see Spore...